On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species - Chan, Tin-Yam; Cleva, Régis; Chu, Ka Hou (Zootaxa, 2016)
The penaeid genus Trachysalambria Burkenroad, 1934a is revised with the aid of sequence data on the 12S and 16S rRNA genes. The species generally reported as “T. longipes” in recent literature was found to be not the true T. longipes (Paul’son, 1875) but a new species, herein named T. dentata sp. nov. To fix the identity of T. longipes, a neotype is selected and this action effectively synonymizes T. villaluzi (Muthu & Motoh, 1979) with T. longipes. Moreover, T. fulva (Dall, 1957) is synonymized with T. malaiana (Balss, 1933) while T. starobogatovi (Ivanov & Hassan, 1976) is confirmed to be a valid species. Two more new species are discovered, with T. parvispina sp. nov., widely distributed in the Indo-West Pacific, and T. crosnieri sp. nov., restricted to Australia. Altogether 12 species are recognized in Trachyalambria. The other valid species in this genus are T. curvirostris (Stimpson, 1860), T. aspera (Alcock, 1905), T. palaestinensis (Steinitz, 1932), T. brevisuturae (Burkenroad, 1934a), T. albicoma (Haysahi & Toriyama, 1980), and T. nansei Sakaji & Hayashi, 2003. Most characters previously used for separating the species of this genus are rather variable and their distinguishing characters are redefined.